The Greek Economy and the Crisis Challenges and Responses - Petrakis, Panagiotis. (Springer Berlin Heidelberg : Imprint: Springer, 2012)
The book “The Greek Economy and the Crisis. Challenges and Responses” targets all those who think about the present and future of this (culturally) long-lived small geographic region (Greece), to form a personal view of its social and economic problems. A society that repeats the same types of behaviour over the centuries does not do so due to random mistakes. It contains intrinsic forces that affect it. These should be understood, to allow us to delineate future developments. However, the manner in which the social and economic process is perceived must be comprehensive and multidisciplinary: Economics, politics, social psychology and organizational psychology are essential to this analysis. Thus, the book is useful to those seeking information for their professional, scientific and personal development, allowing them to shape their social attitude. It is also useful to those responsible for taking decisions at national, European or enterprise level, in relation to the social and economic problems of Greece.